ANALISIS PENGARUH JOB EMBEDDEDNESS DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA PT PURNAMA INDONESIA - OCTAVIA ASTAMARINI, ROSALIA (Jurnal Ilmu Manajemen (JIM), 2018)
This research aims to analyze the effect of job embeddedness and job satisfaction to turnover intention. At the research at PT. Purnama Indonesia uses saturated samples, from all employees are made respondents by 33 respondents, obtained through questionnaire methods and interviews. This type of research is quantitative research. The data analysis technique used in this research is multiple linear regression processed using SPSS Version 20 software. The results of this research indicate that job embeddedness has a positive and insignificant effect on turnover intention, this is inversely proportional to the existing theory, should the attachment be high, the employee will not leave the company, but the facts in the field are different. Even though employees have a bond they can get out from the company any time. For job satisfaction negative and insignificant effect on turnover intention, this is almost the same as the existing theory, but employees who are satisfied still have the desire to leave the company. Then job embeddedness and job satisfaction have positive and insignificant effect on simultaneous turnover intention, from both variables it can be concluded that both of job embeddeness and job satisfaction have an influence on turnover intention even though only a bit. Keywords: job embeddedness; job satisfaction; turnover intention.